Evaluation of Reformer Tubes Degradation after Long Term Operation - Saari, Nurul Aimi (Universiti Teknologi PETRONAS, 2014)
Since the estimation of remnant life by deterministic methods is expensive and time consuming, in this study the remnant life is evaluated using structural reliability analysis and distribution analysis. The remnant life of the reformer tubes was studiedby using the creep lifetime model and Monte Carlo Simulation, based on available data provided through non-destructive in site tests which is Laser-Optic TubeInspection System (LOTIS) and the MANTIS technology consists of combined Eddy Current (ET) and Creep Stain measurement methodologies. The criterion which was used to evaluate the remnant life of the tubes is the service life, wall thickness measurements and minimum wall thickness. Then, the probabilistic variables related to parametric mentioned is gathered and modelled using the probabilistic distribution functions and their adoptable distribution functions were distinguished through simulation develop in Microsoft Excel spreadsheet.